Investigation of Correlation between Communication Skills and Self-Reported Elder Mistreatment in Family Abuse - Zarei, Sogra; Esmaeilpour-Bandboni, Mohammad; Mansour-Ghanaei, Roya; Alizadeh, Iman (Avicenna Journal of Medicine, 2024)
Introduction In today's world, old age has become an important global phenomenon following the increase in life expectancy and the decrease in birth rates. Communication skills are an important requirement in old age. Changing role of the family and existing tensions, mental pressures, and modern life undermine the social position of the elderly and lead to abuse of the elderly by family members. The goal of the present study is to determine the relationship between communication skills and family self-reported domestic abuse among older adult in Iran.Materials and Methods For this cross-sectional-analytical study, 153 elderly adult people admitted in hospitals of the Guilan province were randomly selected. The research instruments were the following questionnaires: demographic characteristics, abbreviated mental test (AMT), the Persian version of Domestic Elder Abuse Questionnaire, family mistreatment of the elderly (Heravy), and Queendom Communication Skill Test–Revise (QCSTR). The data were analyzed by SPSS software (version 22) using descriptive (frequency distribution tables, mean, and standard deviation [SD]) and analytical statistics (Mann–Whitney, Kruskal–Wallis, and Spearman's correlation tests) considering the significance level of 0.05.Results A majority of the elderly were men (51%), were in the age group of 60 to 69 years (72.5%) and married (75.5%), did not hold high school diploma (88.8%), had four to five children (41.2%) with low income (75.9%), and suffered from chronic diseases (68.6%). The mean score of communication skills was 129.09 ± 12.60. The mean score of domestic elder abuse was 2.89 ± 3.97. Communication skills have a significant relationship with age and marital status, but not with sex, education level, income, and chronic disease. There is an inverse correlation between communication skills and domestic elder_abuse (p < 0.001, r = −0.468).Conclusion Communication skills are one of the influential factors of domestic violence. Therefore, to prevent or reduce the amount of violence, it is recommended that family members increase the communication skills of the elderly.
Keywords: older adult; aged; elder abuse; communication; old age; elderly abuse; communication skills